2010
DOI: 10.1099/mic.0.043422-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of GacA in virulence of Vibrio vulnificus

Abstract: The GacS/GacA two-component signal transduction system regulates virulence, biofilm formation and symbiosis in Vibrio species. The present study investigated this regulatory pathway in Vibrio vulnificus, a human pathogen that causes life-threatening disease associated with the consumption of raw oysters and wound infections. Small non-coding RNAs (csrB1, csrB2, csrB3 and csrC) commonly regulated by the GacS/GacA pathway were decreased (P,0.0003) in a V. vulnificus CMCP6 DgacA : : aph mutant compared with the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 76 publications
0
18
0
Order By: Relevance
“…Additional factors have been proposed as potentially associated with virulence, such as phospholipase A (Koo et al, 2007), haemolysin-cytolysin (Gray & Kreger, 1985;Wright & Morris, 1991) and metalloproteases (Gulig et al, 2005). A considerable body of knowledge concerning the virulence mechanisms of V. vulnificus was obtained from mutational analysis experiments using nonhuman cell lines such as mouse intestinal epithelial cells (Jeong & Satchell, 2012), ovarian hamster cells, bovine pulmonary artery cells and peritoneal macrophages from mice (Lee et al, 2004b), or intraperitoneally injected mice (Alice et al, 2008;Gauthier et al, 2010;Kim et al, 2005Kim et al, , 2008Lee et al, 2008b;Shao & Hor, 2000). Nevertheless, it is unclear what is the exact role of the various virulent factors during human infection.…”
Section: Introductionmentioning
confidence: 99%
“…Additional factors have been proposed as potentially associated with virulence, such as phospholipase A (Koo et al, 2007), haemolysin-cytolysin (Gray & Kreger, 1985;Wright & Morris, 1991) and metalloproteases (Gulig et al, 2005). A considerable body of knowledge concerning the virulence mechanisms of V. vulnificus was obtained from mutational analysis experiments using nonhuman cell lines such as mouse intestinal epithelial cells (Jeong & Satchell, 2012), ovarian hamster cells, bovine pulmonary artery cells and peritoneal macrophages from mice (Lee et al, 2004b), or intraperitoneally injected mice (Alice et al, 2008;Gauthier et al, 2010;Kim et al, 2005Kim et al, , 2008Lee et al, 2008b;Shao & Hor, 2000). Nevertheless, it is unclear what is the exact role of the various virulent factors during human infection.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to indirectly regulating carbon metabolism through CsrA, GacA is known to regulate swarming motility and biofilm formation (Goodier & Ahmer, ; Teplitski et al ., a; Gauthier et al ., ). Swarming assays on AB soft (0.4%) agar plates revealed that S. marcescens PDL100 swarms in a branching dendritic pattern (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…When the wild‐type and gacA mutant strains were grown on low molecular weight fractions of coral mucus, the competitive fitness of the wild type increased and led to a relatively equal proportion of each strain in the culture (competitive index = 0.083). Protease activities (as measured on skim milk agar plates) were not different in the mutant and the wild type (data not shown), thus the degradation of the proteinaceous backbone of mucus is not the likely explanation of the observed phenotype, even though gacA orthologs are known to control proteases in other bacteria (Ovadis et al ., ; Cui et al ., ; Gauthier et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This mechanism seems to circumvent the need for GacA, a master regulator that has been shown to act upstream of LasR [9]. The role of GacA in controlling a subset of virulence factors is also known in other microbial pathogens [12], [13]. Indeed, in a C. elegans model of host-microbe interaction involving P. aeruginosa PA14, the role of GacA is very prominent and the pathogenicity of a PA14Δ gacA mutants is significantly abrogated [14].…”
Section: Discussionmentioning
confidence: 99%